2007
DOI: 10.1007/s11090-007-9087-x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of organic dyes in water by electrical discharges

Abstract: The degradation of several organic compounds in aqueous solution: methyl yellow (C 14 H 15 N 3 ), methyl red (C 15 H 15 N 3 O 2 ), methyl orange (C 14 H 14 N 3 NaO 3 S), phenol red (C 19 H 14 O 5 S) and methylene blue (C 16 H 18 ClN 3 S), was investigated in a pulsed corona discharge. High voltage pulses of 17 kV amplitude, 24 ns rise time and approximately 200 ns duration (full width at half maximum--FWHM) were applied to an array of six hollow needles. When oxygen was bubbled into the solution through the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 18 publications
(33 reference statements)
3
44
0
4
Order By: Relevance
“…H 2 O 2 was also measured since it is a well-known oxidizing species which can react non-selectively with organic pollutants [13]. In our experiments, the increase in treatment duration led to a rise in H 2 O 2 concentration; and at a given time, its concentration was in the same range whatever the inlet gas, as indicated in Table 1.…”
Section: Generated Productssupporting
confidence: 51%
“…H 2 O 2 was also measured since it is a well-known oxidizing species which can react non-selectively with organic pollutants [13]. In our experiments, the increase in treatment duration led to a rise in H 2 O 2 concentration; and at a given time, its concentration was in the same range whatever the inlet gas, as indicated in Table 1.…”
Section: Generated Productssupporting
confidence: 51%
“…Futamura and Yamamoto [7] suggest that TCE dissociation is initiated by elimination of chlorine or hydrogen atoms from excited TCE. Secondary decomposition of TCE can be induced by radicals formed from the initial decomposition, which explains the similar or even higher decomposition efficiency obtained for higher initial concentrations of TCE [7,20].…”
Section: Reaction Products Of Tce Decompositionmentioning
confidence: 71%
“…The effect of residence time on TCE oxidation was investigated in Ref. [20] by varying the flow rate (200-510 sccm) while keeping the same electrode configuration. It was found that the residence time did not influence TCE conversion over the range of input energies used (120-2330 J/l).…”
Section: Tce Decomposition In the Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a multiple bubble jet system encapsulating O 3 in small bubbles, O and OH radicals generated by a DC pulsed discharge was successfully constructed for decolorizing a methylene blue solution (12)- (15) . Bubble jet dynamics with luminescence and complex streamer behavior inside an argon bubble were successfully visualized.…”
Section: Introductionmentioning
confidence: 99%